SYNTHESIS OF SULFUR CONTAINING ORGANIC COMPOUNDS BY REACTION OF THIOL-EN AND THIOL-IN - Arslanov, Akmaljon; Erkinov, Rasuljon; Soliyev, Makhammadzhon (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
The mechanism of radical reaction and addition processes were analyzed, and their significance in polymer, pharmaceutical, agricultural, and other fields was presented. The research investigated the conditions and mechanism for obtaining sulfur-containing organic compounds, such as thioethers and sulfides, formed as a result of reactions of alkenes and alkynes with substances with thiol groups. At the same time, this serves as an important scientific-theoretical and practical basis for the further development of the synthesis of sulfur-containing organic compounds and the development of environmentally friendly and effective technologies.